The Experiential Learning Model in Social Studies Instruction to Improve Learning Outcomes at Elementary School - Cornelia Narahawarin; Samuel P. Ritiauw (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Social Studies learning at the elementary school level faces challenges due to low student learning outcomes caused by passive, conventional instructional methods. This study aims to improve the learning outcomes of fifth-grade students at SD Negeri 1 Passo through the experiential learning model. Utilizing a Classroom Action Research design across two cycles, this study involved 19 students. Data were collected through learning outcome tests and observation sheets, then analyzed using descriptive quantitative techniques. The findings demonstrated progressive improvement: the class average rose from 57.73 (Poor) in the pre-test to 68.6 (Sufficient) in Cycle I and reached 81.5 (Good) in Cycle II. The model eliminated the Poor and Very Poor categories starting from Cycle I, culminating in a 100% classical completion rate in Cycle II, where 52.63% of students achieved the good category and 47.37% reached Very Good. Furthermore, optimizing the abstract conceptualization and active experimentation stages effectively strengthened higher-order thinking skills (HOTS), evidenced by a significant score increase in the highest-weight assessment aspect from 50.10% to 37.1 (out of 50). This study concludes that from a constructivist perspective, the experiential learning model exerts a transformative impact by habituating a systematic learning cycle, integrating concrete experiences, reflective observation, conceptualization, and practical application. This approach actively constructs student understanding and successfully bridges abstract social studies concepts into meaningful, applicable knowledge for elementary school students.